Digital Marketing in the Business Environment - Ištvanić, Marin; Dominika Crnjac Milić; Krpić, Zdravko (International Journal of Electrical and Computer Engineering Systems, 2018)
Promotion of products has become an increasingly important component in the new digital age, mostly thanks to digital marketing. The traditional form of marketing is lagging behind digital marketing, which offers users new opportunities like personalized messages or answers to a search query. There are several ways to advertise on the internet, and in this paper, ways and tools will be presented that allow digital advertising as well as their advantages and disadvantages. Specifically, search engine optimization, search engine marketing, display advertising, social networking marketing and e-mail marketing will be discussed. Also, the goal of the paper is to enable more efficient creation and implementation of similar contents in new business environments through an insight into internet advertising, social and business networks.